Sub-National Constitutions in Ethiopia: Towards Entrenching Constitutionalism at State Level - Regassa, T (Mizan law review, 2010)
Ethiopia’s federalism is often studied from the perspective of the “centre”.1 The result of this focus on the centre to start off our inquiries has rendered the state constitutions 2 invisible both in academic and non-academic circles.3 This article offers a fresh look at the Ethiopian federal experiment from the perspective of the states. In a sense, therefore, this study is an attempt at studying federalism “from below”.4 Thus this paper offers an overview of state constitutions in Ethiopia with a view to highlighting their significance in the public life of Ethiopians. It also provides an analysis of how we can deepen and entrench constitutionalism in the states of Ethiopia through the instrumentality of state constitutions.